Endovascular Management of Thrombosed Dialysis Vascular Circuits - Almehmi, Ammar; Sheta, Mohamed; Abaza, Masa; Almehmi, Sloan E.; El Khudari, Husam; Shaikh, Aisha (Seminars in Interventional Radiology, 2022)
A functional hemodialysis vascular access is the lifeline for patients with end-stage kidney disease and is considered a major determinant of survival and quality of life in this patient population. Hemodialysis therapy can be performed via arteriovenous fistulas, arteriovenous grafts, and central venous catheters (CVCs). Following dialysis vascular access creation, the interplay between several pathologic mechanisms can lead to vascular luminal obstruction due to neointimal hyperplasia with subsequent stenosis, stasis, and eventually access thrombosis. Restoration of the blood flow in the vascular access circuit via thrombectomy is crucial to avoid the use of CVCs and to prolong the life span of the vascular access conduits. The fundamental principles of thrombectomy center around removing the thrombus from the thrombosed access and treating the underlying culprit vascular stenosis. Several endovascular devices have been utilized to perform mechanical thrombectomy and have shown comparable outcomes. Standard angioplasty balloons remain the cornerstone for the treatment of stenotic vascular lesions. The utility of drug-coated balloons in dialysis vascular access remains unsettled due to conflicting results from randomized clinical trials. Stent grafts are used to treat resistant and recurrent stenotic lesions and to control extravasation from a ruptured vessel that is not controlled by conservative measures. Overall, endovascular thrombectomy is the preferred modality of treatment for the thrombosed dialysis vascular conduits.
Keywords: arteriovenous; graft; fistula; declot; thrombectomy; device; stent; balloon; access; interventional radiology